Treatment of osteoarthritis of large and small joints using an injectable complex action chondroprotector - I. V. Menshikova; V. N. Sorotskaya (Лечащий Врач)
The aim of the study was to assess the efficacy and tolerability of slow-acting injectable agent for the treatment of osteoarthritis in the treatment of osteoarthritis of large and small joints. The study group consisted of 49 patients (87,8% women, 12,2% men, whose median age – 63,4 [52,3; 75,2] years, the duration of the disease – 5,86 [3,07; 11.4] years, body mass index – 30,06 [23,1; 41,4] kg/m2): 14,6% – with damage to small joints of the hands (group 1), 62,5% with damage to large joints, who received the drug only intramuscularly (group 2) and 22,9% with lesions of large joints, who received the drug intra-articularly and intramuscularly (group 3). During the year, 2 courses of injections were carried out with an interval of 6 months. 3 months follow-up period was held. The results of treatment were assessed by the dynamics of the VAS of pain, AUSCAN and WOMAC indices, patient and doctor satisfaction on a 5-point scale, and the need for non-steroidal anti-inflammatory drugs (NSAIDs). After 1 course of treatment, there was a statistically significant decrease in pain according to VAS in all groups by 45,4-57,7%, in the AUSCAN index – by 49,3%, in the WOMAC index in group 2 – by 44,9%, in group 3 – by 53,2%. About 1/3 of patients refused to take NSAIDs. By the beginning of the 2nd course, these indicators increased, but not to the initial level. After the 2nd course of therapy, further improvement was noted pain according to VAS – by 20,2-30,8%, AUSCAN index – by 28,4%, WOMAC index in group 2 – by 20,5%, in group 3 – by 22 ,9%. After 3 months of follow-up there was a decrease in comparison with the initial indicators: pain according to VAS – by 60,8-64,8%, AUSCAN index – by 34,3%, WOMAC in group 2 – by 51,3%, in group 3 – by 35,4%. The dynamics of joint stiffness was most pronounced. Half of the patients stopped taking NSAIDs. Adverse reactions (dermatitis at the injection site and synovitis after i/a administration of the drug) were detected in 2 patients.